(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
Polyurethane (PU) foam is widely used as an insulation material; however, its porous structure increases susceptibility to microbial growth. This study compares the effects of clove leaf powder and clove oil (Syzygium aromaticum) as natural additives on the density, crystallinity, and antimicrobial activity of PU foam. PU foam was synthesized via a one-shot method using a polyol-to-isocyanate ratio of 1:1.6, followed by the incorporation of clove leaf powder (0–5 wt%) and clove oil (0–15 wt%). Density was measured, crystallinity was analyzed using Differential Scanning Calorimetry (DSC), and antimicrobial activity was evaluated against Escherichia coli. The addition of clove leaf powder decreased density due to non-uniform pore formation, whereas clove oil increased density, reaching approximately 0.067 g/cm³ at 15 wt%. Crystallinity increased with both additives; however, clove oil provided a more consistent enhancement, while clove leaf powder increased crystallinity up to 15%. Antimicrobial activity was observed in all modified samples, with enhanced antimicrobial effectiveness for clove oil. Overall, clove oil outperforms clove leaf powder in improving the structural and antimicrobial properties of PU foam.